Kekuatan Sidik Jari sebagai Alat Bukti dalam Mengungkap Suatu Tindak Pidana Pembunuhan - Suhamdani, Nadila Novanty; Andiani, Natalie Puspita; Wahyudinanty, Rayhani; Hosnah, Asmak Ul (AHKAM, 2023)
Fingerprints are one of the pieces of evidence used to uncover crime problems. Fingerprints are used for the process of identifying a person. Analytical descriptive is the method used in research, implying that the discussion is carried out by presenting and discussing (explaining) the data as a whole, followed by an analysis of evidence using legal science theories. This writing attempts to answer the problem regarding the role of fingerprints in resolving the crime of murder and how the strength of fingerprints is in proving the crime of murder. Based on this research it was found that fingerprints are part of the Criminal Procedure Code and Law no. 2 of 2002 which regulates the police limiting the use of evidence by law enforcers in criminal prosecutions. The use of fingerprint evidence in the prosecution of murder cases is a strategic tool for law enforcement.